Research Review of Electric Drive Axle - Jianfei Huang; Jianhua Wang; Di Jin; Zongze Wang (Jixie chuandong)
As the core component of electric vehicles， electric drive axles directly determine the performance of electric vehicles. A comprehensive review of the structure of single-speed and multi-speed electric drive axles is carried out. Firstly， the basic structures of single-speed and multi-speed electric drive axles are explained respectively. Then， the research status of multi-speed electric drive axles is summarized. Finally， the advantages and disadvantages of single-speed and multi-speed electric drive axles are compared， and it is clear that multi-speed is the development trend. On this basis， it is pointed out that the focus of future research is that increasing the degree of integration while the multi-speed.